Agent-Based Spatial Competition - Eveline van Leeuwen; Mark Lijesen (European Regional Science Association (ERSA), 2012)
Equilibrium in the Hotelling model of spatial competition is guaranteed if the distribution of consumers is log concave. In the real world, nothing guarantees such a log concave distribution however, rendering the analytical model unable to provide a primer as to what one might expect from empirical applications. We develop an agent-based model of spatial competition that is capable of reproducing the results of the analytical model and also provides meaningful results for some cases where the distribution of consumers is not log concave. Using numerous simulations, on randomly drawn distributions, we derive equilibrium locations and prices and test for uniqueness. Moreover, we check whether the relationships between characteristics of the distribution (e.g. concentration, skewness) and outcomes are consistent with the analytical model. : Hotelling, agent-based modelling, spatial competition
Keywords: 330